解方程:x+z=y (1) ,7z-(x+y)=2 (2) ,x+y+z=14 (3)
解方程:{2x+3y+z=7,x+y+z=4,3x+y-z=-4
解方程一;{x+y-z=6,x-3y+2z=1,3x+2y-z=-7.②{3x+4z=7,2x+3y+z=9,5x-9y
试证明(x+y-2z)+(y+z-2x)+(z+x-2y)=3(x+y-2z)(y+z-2x)(z+x-2y)
x:y:z=1:2:3 x+2y+3z=56解方程
x+2y+3z=28 x:y:z=1:2:3 解方程
3x-y+z=3 2x+y-3z=11 x+y+z=12 解方程
解方程{3x -y+z=4 2x+3y-z=12 x+y+z=6
{x+y+z=1;x+3y+7z=-1;z+5y+8z=-2
解方程组x+2y-z=1 ,3x-3y+z=2,2x+3y+z=7和方程组x+y=-14,y+z=-7,x+z=19
已知2x+3y+z=130,3x+5y+z=180,试求x+2y/z+y+z【在线等高手解方程】
x/2=y/3=z/5 x+3y-z/x-3y+z
解方程:3x+2y+z=315 x+2y+3z=285